Climate analogues tool an approach to mitigate climate change - Muhammed, U P Faras Bin; Kandiannan, K; Krishnamurthy, K S (Indian Farming, 2019)
Climate analogues approach allows researchers to identify, connect and map sites with statistically similar climates across space and time. The approach has the potential to be applied in agricultural policy and planning and provides a novel way to support climate change adaptation in the agricultural sector. Climate Change, Agriculture and Food Security (CCAFS) have provided an online platform (the Climate Analogues Tool) for quick, easily accessible and userfriendly applications of the Climate Analogues approach.